Dynamical evolution of massive black hole pairs in the presence of spin-dependent radiative feedback. Issue 3 (2nd February 2023) - Bollati, Francesco; Lupi, Alessandro; Dotti, Massimo; Haardt, Francesco
ABSTRACT: The putative ubiquity of massive black holes (MBHs) at the centre of galaxies, and the hierarchical progress of structure formation along the cosmic history, together necessarily imply the existence of a large population of cosmic MBH binaries. Such systems are understood to be the loudest sources of gravitational waves at MHz frequencies, the regime that will be probed by the next Laser Interferometer Space Antenna. It has been proposed that the rate at which MBHs pair and then bind to form binaries is critically dependent upon the feedback exerted by the MBHs on the surrounding gaseous environment. Using the publicly available code gizmo, we perform a suite of simulations aimed at studying the dynamics of an MBH pair embedded in a gaseous disc on ∼100-pc scale. By means of dedicated modules, we follow the dynamics of MBHs in the presence of different spin-dependent radiative feedback models, and compare the results to a benchmark case with no feedback at all. Our main finding is that feedback causes the secondary MBH to shrink its orbit at a reduced pace, when compared with models where feedback is absent. Moreover, such slower inspiral occurs on eccentric orbits, as feedback has the net effect of hampering the circularization process. Though idealized in many aspects, our study highlights and quantities the importance of including spin-dependent feedback recipes in hydrodynamic simulations of MBH pairs, and ultimately in assessing the cosmological coalescence rate of such systems in view of their detection through gravitational waves.